Method for large-scale preparation of metal monatomic covalent organic framework material and application thereof in ammonia gas adsorption separation

CN122978377APending Publication Date: 2026-10-27FUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611119807.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

这些氨分子不仅会不可逆中和膜电极的磺酸基团,导致质子传导率骤降,还会牢固占据铂催化剂活性位点,引起电池性能的快速衰减

Benefits of technology

(1)突破性的吸附性能:本发明所制备的材料展现出卓越的氨气吸附能力,在298K、1.0 bar条件下吸附容量可达5.9-13.5 mmol/g。更值得注意的是,每个铜离子能够通过协同吸附机制捕获超过14个氨分子,这种多分子吸附行为突破了传统化学计量比的限制。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978377A_ABST
    Figure CN122978377A_ABST
Patent Text Reader

Abstract

The application discloses a large-scale preparation method of metal monatomic covalent organic framework material and application of the material in ammonia adsorption and separation. The material takes an alkali nitrogen-rich olefinic bond connected covalent organic framework as a carrier, builds high accessible metal monatomic sites through metastable metal-nitrogen coordination, and realizes multi-molar ammonia adsorption. The material is integrated in an ammonia-hydrogen fuel cell system as a front adsorbent, can deeply remove trace NH3 concentration in fuel gas from 100 ppm to less than 0.1 ppm, and exhibits high selectivity, rapid adsorption kinetics and excellent cycle stability. When applied to a proton exchange membrane fuel cell, the peak power density is increased from 0.45 W cm ‑2 to 1.1 W cm ‑2 The above, the stable operation time under 1 A·cm ‑2 Current density is prolonged to more than 120 minutes, and the battery durability and operation efficiency are significantly enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of nanomaterials and energy chemical technology, specifically relating to a method for the large-scale preparation of metal single-atom covalent organic framework materials and their application in ammonia adsorption and separation. Background Technology

[0002] Single-atom materials, as a cutting-edge research direction in heterogeneous catalysis and adsorption separation, exhibit enormous potential by maximizing the utilization efficiency of metal atoms. These materials can achieve atomic-level dispersion of active sites, providing an ideal research platform for controlling material properties at the atomic scale. However, existing single-atom materials generally employ a rigid anchoring strategy, statically fixing metal atoms to the support surface by constructing strong chemical bonds with high coordination numbers. While this strategy enhances stability, it inevitably sacrifices the dynamic adaptability of the sites, becoming a bottleneck restricting breakthroughs in material performance. In the field of adsorption separation, the limitations of static single-atom materials are particularly prominent. The near-saturated coordination environment and poor accessibility limit the adsorption capacity of a single metal site to a simple stoichiometric range, and the capture precision is insufficient.

[0003] In ammonia-hydrogen energy systems, ammonia serves as an ideal hydrogen carrier. However, trace amounts of ammonia gas (50-200 ppm) remaining in its catalytic decomposition products can severely damage proton exchange membrane fuel cells. These ammonia molecules not only irreversibly neutralize the sulfonic acid groups on the membrane electrode assembly, leading to a sharp drop in proton conductivity, but also firmly occupy the active sites of the platinum catalyst, causing rapid performance degradation. Currently used traditional adsorbents such as zeolites and activated carbon are insufficient to meet the stringent requirements of fuel cell systems. While zeolites possess strong ammonia adsorption capacity, they suffer from desorption difficulties and poor hydrothermal stability; activated carbon, relying on physical adsorption mechanisms, exhibits insufficient selectivity and capacity for trace ammonia.

[0004] In summary, traditional single-atom materials suffer from low exposure and poor accessibility of active sites, and their adsorption capacity is constrained by inherent stoichiometry. Existing covalent organic framework materials generally suffer from high synthesis costs, difficulty in large-scale mass production, and poor stability in acid and alkali media. Commercial industrial adsorbents lack sufficient precision in capturing and separating trace amounts of ammonia, failing to meet the stringent purification requirements of fuel cell systems. Currently, the industry lacks dedicated ammonia adsorption materials that simultaneously possess high-density active sites, rapid adsorption kinetics, and excellent cycle stability. Therefore, developing adsorbents that combine high-density active sites, dynamic recognition capabilities, and stability has become a key challenge in promoting the development of ammonia-hydrogen energy technology. Summary of the Invention

[0005] The purpose of this invention is to overcome the technical bottlenecks of existing adsorption materials in the field of ammonia capture, and to provide a method for the large-scale preparation of metal single-atom covalent organic framework materials and their application in ammonia adsorption and separation.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing a metal single-atom covalent organic framework material, comprising the following steps: (1) 2,4,6-trimethylpyridine, terephthalaldehyde, benzoic anhydride and benzoic acid were reacted under nitrogen protection for a period of time. After the reaction was completed, the mixture was cooled to room temperature. The resulting solid was soaked, purified and dried to obtain a covalent organic framework material. (2) The covalent organic framework material is mixed with the metal salt in a solvent and impregnated. Then, after centrifugation, washing and drying, a metal single-atom covalent organic framework material is obtained.

[0007] The metal single-atom covalent organic framework material uses sp 2 Using carbon-conjugated olefins linked to covalent organic frameworks as supports, metal single atoms are anchored to the nitrogen coordination sites of the framework through a precisely controlled impregnation process. The support possesses a regular pore structure, high specific surface area, and abundant basic nitrogen functional groups, providing an ideal platform for the uniform dispersion of metal single atoms. This invention synthesizes well-crystallized COFs supports via green melt polymerization, followed by metal impregnation under mild conditions. Precise control of the metal loading is achieved by adjusting the washing process parameters. This method avoids high-temperature heat treatment or complex post-modification steps, effectively maintaining the structural integrity of the support while ensuring atomic-level dispersion of metal species.

[0008] Furthermore, the molar ratio of 2,4,6-trimethylpyridine, terephthalaldehyde, benzoic anhydride and benzoic acid in step (1) is 0.2-0.4:0.3-0.6:0.2-0.4:0.02-0.04.

[0009] Furthermore, the reaction time in step (1) is 3-7 days, and the reaction temperature is 160-200℃.

[0010] Furthermore, the metal salt mentioned in step (2) is a chloride, nitrate, acetate or sulfate of copper, zinc or cobalt.

[0011] Furthermore, the immersion temperature in step (2) is 0-50 ℃, the stirring speed is 500-1500 rpm, and the treatment time is 1-48 hours.

[0012] Furthermore, the solvent mentioned in step (2) is one or more of methanol, ethanol or isopropanol.

[0013] Secondly, this invention provides a metal single-atom covalent organic framework adsorbent material, prepared by the above-described method. The material comprises a covalent organic framework support and metal single atoms anchored thereto; wherein the metal single atoms and the framework nitrogen atoms form a metastable coordination structure capable of configurational migration during ammonia adsorption. Furthermore, the well-ordered pore structure of the COFs promotes mass transfer and diffusion of ammonia molecules, the high density of metastable single-atom sites provides highly active and strong binding sites, and the rigid structure of the framework ensures the long-term stability of the material. This multi-level structural design enables the material to achieve adsorption capacities exceeding traditional stoichiometric ratios while maintaining high selectivity.

[0014] Furthermore, the loading amount of the metal single atom on the covalent organic framework support is 1.5wt%-20wt%.

[0015] Thirdly, the present invention provides the application of the above-mentioned metal single-atom covalent organic framework material in gas adsorption or separation, wherein the gas is ammonia; the application is to separate or capture ammonia from a mixed gas, wherein the mixed gas is the tail gas from the decomposition of ammonia to produce hydrogen, and contains hydrogen, nitrogen and trace ammonia; wherein the concentration of the trace ammonia is 50-200 ppm.

[0016] Fourthly, this invention provides the application of the aforementioned metal single-atom covalent organic framework material in proton exchange membrane fuel cells. By integrating the metal single-atom covalent organic framework material into the fuel gas purification unit, a highly efficient trace ammonia purification system is constructed. This application not only solves the problem of ammonia poisoning of fuel cell catalysts but also significantly improves the operating efficiency and reliability of the entire energy system.

[0017] Compared with the prior art, the present invention has the following outstanding advantages: (1) Breakthrough adsorption performance: The material prepared by this invention exhibits excellent ammonia adsorption capacity, with an adsorption capacity of 5.9-13.5 mmol / g under the conditions of 298 K and 1.0 bar. More notably, each copper ion can capture more than 14 ammonia molecules through a synergistic adsorption mechanism, and this multi-molecular adsorption behavior breaks through the limitations of traditional stoichiometry.

[0018] (2) Excellent selective separation performance: The material exhibits extremely high separation selectivity for the ammonia / nitrogen system, with an IAST selectivity of up to 1335. In the dynamic breakthrough experiment, the material achieved a complete breakthrough time of 440 minutes for a low concentration of 100 ppm ammonia, demonstrating its excellent trace gas capture capability.

[0019] (3) Significant advantages in scalability: Based on low-cost precursors (such as trimethylpyridine) and a simple process route, the material can be prepared on a scale of hundreds of grams. This scalability provides a solid foundation for industrial applications and solves the key bottleneck in the industrialization of traditional COFs materials.

[0020] (4) Excellent stability and cycling performance: After 30 adsorption-desorption cycles, the material retains more than 97% of its capacity, and its crystal structure and pore characteristics are completely preserved. This excellent cycling stability ensures the reliability of the material during long-term operation.

[0021] (5) Significant practical application results: In a simulated ammonia-hydrogen fuel cell system, the material can purify the ammonia concentration in the fuel gas from 50-200 ppm to below 0.1 ppm. After integrating this material, the peak power density of the proton exchange membrane fuel cell increased from 0.45 W·cm³. -2 Increased to 1.1 W·cm -2 Above, and within 1 A·cm -2 The stable operating time under current density is extended to more than 120 minutes.

[0022] (6) Green and environmentally friendly characteristics: The entire preparation process does not require the use of toxic solvents or complex equipment, and the materials can be recycled and reused multiple times, which is in line with the concepts of green chemistry and sustainable development. Attached Figure Description

[0023] Figure 1 The X-ray diffraction patterns are those of the adsorbent materials prepared in Examples 1-3 and Comparative Example 1.

[0024] Figure 2 The images show (a) N2 adsorption-desorption isotherms and (b) pore size distribution diagrams of the adsorbent materials prepared in Examples 1-3 and Comparative Example 1.

[0025] Figure 3 The NH3 adsorption isotherms of the adsorbent materials prepared in Examples 1-3 and Comparative Example 1 at 25 °C and 1.0 bar are shown.

[0026] Figure 4 The material is the 100-gram-scale adsorbent A prepared in Example 1.

[0027] Figure 5 The image shows an aberration-corrected HAADF-STEM image of the adsorbent A material prepared in Example 1, where red circles mark copper species existing in single-atom form.

[0028] Figure 6 The images show (a) Cu K-edge XANES and (b) FT-EXAFS spectra of the adsorbent A material prepared in Example 1.

[0029] Figure 7 The dynamic breakthrough curves of the adsorbents prepared in Examples 1-3 and Comparative Examples 1-3 for H2 / N2 mixtures containing 100 ppm NH3 at 25 °C are shown.

[0030] Figure 8 The graph shows the change in NH3 capacity of the adsorbent C material prepared in Example 3 during 30 adsorption-desorption cycles.

[0031] Figure 9 A performance comparison chart of an ammonia-hydrogen fuel cell system integrating adsorbent A prepared in Example 1. Detailed Implementation

[0032] The present invention will be further described in detail below with reference to specific embodiments. The specific implementation methods described herein are for illustration and explanation only and are not intended to limit the present invention.

[0033] Example 1 2,4,6-Trimethylpyridine (TM, 49.0 mL, 0.4 mol), terephthalaldehyde (TP, 80.4 g, 0.6 mol), benzoic anhydride (90.2 g, 0.4 mol), and benzoic acid (4.88 g, 0.04 mol) were weighed and placed in a 500 mL reaction vessel. The mixture was sonicated for 10 minutes to ensure thorough dispersion. The reaction vessel was then sealed and, under nitrogen protection, stirred in an oil bath at 180 °C for 5 days. After the reaction, the mixture was cooled to room temperature. The resulting solid was soaked in an ammonia-DMF (V / V = 1:1) mixture for one day, followed by purification using a Soxhlet extractor with a methanol and acetone (V / V = 1:1) mixture for one day. The solid was then dried under vacuum at 80 °C for 12 hours to obtain well-crystallized COF. TMTP Powder. Then COF TMTP Powder (100 g) and CuCl2·2H2O (132 g, 0.77 mol) were added separately to 15 L of anhydrous ethanol. The two solutions were then mixed and stirred at 25 °C and 1000 rpm for 12 hours. After centrifugation, the resulting product was washed with 100 L of methanol and dried under vacuum at 80 °C for 12 hours to obtain adsorbent A. The actual copper loading was determined to be 1.5 wt% by ICP-OES.

[0034] Example 2 Weigh 2,4,6-trimethylpyridine (TM, 24.5 μL, 0.2 mmol), terephthalaldehyde (TP, 40.2 mg, 0.3 mmol), benzoic anhydride (45.1 mg, 0.2 mmol), and benzoic acid (2.44 mg, 0.02 mmol) into a 10 mL heat-resistant glass tube. Sonicate for 10 minutes to ensure complete dispersion, then remove oxygen from the glass tube through three freeze-evacuation-thawing cycles and seal. Incubate the reaction mixture at 180 °C for 5 days. After the reaction, cool to room temperature, soak the resulting solid in an ammonia-DMF mixture (V / V = 1:1) for one day, then purify it for one day using a Soxhlet extractor with a methanol and acetone mixture (V / V = 1:1), and finally dry under vacuum at 80 °C for 12 hours to obtain well-crystallized COF. TMTP Powder. Then COF TMTP Powder (50 mg) and CuCl2·2H2O (66 mg, 0.39 mmol) were added separately to 7.5 mL of anhydrous ethanol. The two solutions were then mixed and stirred at 25 °C and 1000 rpm for 12 hours. After centrifugation, the resulting product was washed with 25 mL of methanol and dried under vacuum at 80 °C for 12 hours to obtain adsorbent B. The actual copper loading was determined to be 3.0 wt% by ICP-OES.

[0035] Example 3 2,4,6-Trimethylpyridine (TM, 24.5 μL, 0.2 mmol), terephthalaldehyde (TP, 40.2 mg, 0.3 mmol), benzoic anhydride (45.1 mg, 0.2 mmol), and benzoic acid (2.44 mg, 0.02 mmol) were placed in a 10 mL heat-resistant glass tube. The tube was sonicated for 10 minutes to ensure complete dispersion. Oxygen was then removed from the tube through three freeze-evacuation-thawing cycles, and the tube was sealed. The reaction mixture was placed at 180 °C for 5 days. After the reaction, the mixture was cooled to room temperature, and the resulting solid was soaked in an ammonia-DMF (V / V = 1:1) mixture for one day. It was then purified for one day using a Soxhlet extractor with a methanol and acetone (V / V = 1:1) mixture, and dried under vacuum at 80 °C for 12 hours to obtain well-crystallized COF. TMTP Powder. Then COF TMTP Powder (50 mg) and CuCl2·2H2O (66 mg, 0.39 mmol) were added separately to 7.5 mL of anhydrous ethanol. The two solutions were then mixed and stirred at 25 °C and 1000 rpm for 12 hours. After centrifugation, the resulting product was washed with 12.5 mL of methanol and dried under vacuum at 80 °C for 12 hours to obtain adsorbent C. The actual copper loading was determined to be 4.8 wt% by ICP-OES.

[0036] Example 4 2,4,6-Trimethylpyridine (TM, 24.5 μL, 0.2 mmol), terephthalaldehyde (TP, 40.2 mg, 0.3 mmol), benzoic anhydride (45.1 mg, 0.2 mmol), and benzoic acid (2.44 mg, 0.02 mmol) were placed in a 10 mL heat-resistant glass tube. The tube was sonicated for 10 minutes to ensure complete dispersion. Oxygen was then removed from the tube through three freeze-evacuation-thawing cycles, and the tube was sealed. The reaction mixture was placed at 180 °C for 5 days. After the reaction, the mixture was cooled to room temperature, and the resulting solid was soaked in an ammonia-DMF (V / V = 1:1) mixture for one day. It was then purified for one day using a Soxhlet extractor with a methanol and acetone (V / V = 1:1) mixture, and dried under vacuum at 80 °C for 12 hours to obtain well-crystallized COF. TMTP Powder. Then COF TMTP Powder (50 mg) and ZnCl2 (52 mg, 0.39 mmol) were added separately to 7.5 mL of anhydrous ethanol. The two solutions were then mixed and stirred at 25 °C and 1000 rpm for 12 hours. After centrifugation, the resulting product was washed with 50 mL of methanol and dried under vacuum at 80 °C for 12 hours to obtain adsorbent D. The actual zinc loading was determined to be 2.2 wt% by ICP-OES.

[0037] Comparative Example 1 Weigh 2,4,6-trimethylpyridine (TM, 24.5 μL, 0.2 mmol), terephthalaldehyde (TP, 40.2 mg, 0.3 mmol), benzoic anhydride (45.1 mg, 0.2 mmol), and benzoic acid (2.44 mg, 0.02 mmol) into a 10 mL heat-resistant glass tube. Sonicate for 10 minutes to ensure complete dispersion, then remove oxygen from the tube using three freeze-evacuation-thawing cycles and seal. Incubate the reaction mixture at 180 °C for 5 days. After the reaction, cool to room temperature, soak the resulting solid in an ammonia-DMF (V / V = 1:1) mixture for one day, then purify it for one day using a Soxhlet extractor with a methanol and acetone (V / V = 1:1) mixture. Dry under vacuum at 80 °C for 12 hours to obtain adsorbent E.

[0038] Comparative Example 2 Weigh 2,4,6-trimethylpyridine (TM, 24.5 μL, 0.2 mmol), 4,4'-biphenyldicarboxaldehyde (BP, 63 mg, 0.3 mmol), benzoic anhydride (45.1 mg, 0.2 mmol), and benzoic acid (2.44 mg, 0.02 mmol) into a 10 mL heat-resistant glass tube. Sonicate for 10 minutes to ensure complete dispersion, then remove oxygen from the glass tube through three freeze-evacuation-thawing cycles and seal. Incubate the reaction mixture at 180 °C for 5 days. After the reaction, cool to room temperature, soak the resulting solid in an ammonia-DMF (V / V = 1:1) mixture for one day, then purify it for one day using a Soxhlet extractor with a methanol and acetone (V / V = 1:1) mixture. Dry under vacuum at 80 °C for 12 hours to obtain well-crystallized COF. TMBP Powder. Then COF TMBP Powder (50 mg) and CuCl2·2H2O (66 mg, 0.39 mmol) were added separately to 7.5 mL of anhydrous ethanol. The two solutions were then mixed and stirred at 25 °C and 1000 rpm for 12 hours. After centrifugation, the mixture was washed with 50 mL of methanol and dried under vacuum at 80 °C for 12 hours to obtain adsorbent F. The actual copper loading was determined to be 2.4 wt% by ICP-OES.

[0039] Comparative Example 3 2,4,6-Trimethylpyridine (TM, 24.5 μL, 0.2 mmol), 2,2'-bipyridine-5,5'-dicarboxaldehyde (BY, 63.6 mg, 0.3 mmol), benzoic anhydride (45.1 mg, 0.2 mmol), and benzoic acid (2.44 mg, 0.02 mmol) were weighed and placed in a 10 mL heat-resistant glass tube. The tube was sonicated for 10 minutes to ensure thorough dispersion. Oxygen was then removed from the tube through three freeze-evacuation-thawing cycles, and the tube was sealed. The reaction mixture was placed at 180 °C for 5 days. After the reaction, the mixture was cooled to room temperature. The resulting solid was soaked in an ammonia-DMF (V / V = 1:1) mixture for one day, followed by purification using a Soxhlet extractor with a methanol and acetone (V / V = 1:1) mixture for one day. The solid was then dried under vacuum at 80 °C for 12 hours to obtain well-crystallized COF. TMBY Powder. Then COF TMBYPowder (50 mg) and CuCl2·2H2O (66 mg, 0.39 mmol) were added separately to 7.5 mL of anhydrous ethanol. The two solutions were then mixed and stirred at 25 °C and 1000 rpm for 12 hours. After centrifugation, the resulting product was washed with 50 mL of methanol and dried under vacuum at 80 °C for 12 hours to obtain adsorbent G. The actual copper loading was determined to be 8.2 wt% by ICP-OES.

[0040] Comparative Example 4 Weigh 1,3,5-tris(4-aminophenyl)benzene (TA, 119 mg, 0.33 mmol), 2,6-dicarboxypyridine (DP, 68 mg, 0.5 mmol), mesitylene (3 mL), 1,4-dioxane (4 mL), and 6 M acetic acid solution (0.5 mL) into a 10 mL heat-resistant glass tube. Sonicate for 10 minutes to ensure complete dispersion. Then, remove oxygen from the glass tube through three freeze-evacuation-thawing cycles and seal the tube. Incubate the reaction mixture at 120 °C for 3 days. After the reaction, cool to room temperature and purify using a Soxhlet extractor with a methanol and acetone (V / V = 1:1) mixture for one day. Dry under vacuum at 80 °C for 12 hours to obtain well-crystallized COF. TADP Powder. Then COF TADP Powder (50 mg) and CuCl2·2H2O (66 mg, 0.39 mmol) were added to 7.5 mL of anhydrous ethanol, stirred at 1000 rpm for 12 hours at 25 °C, then centrifuged. The resulting product was washed with 50 mL of methanol and dried under vacuum at 80 °C for 12 hours to obtain adsorbent H. The actual copper loading was determined to be 11.2 wt% by ICP-OES.

[0041] Comparative Example 5 2,4,6-trimethyl-1,3,5-triazine (TT, 24.6 mg, 0.2 mmol), 2,2'-bipyridine-5,5'-dicarboxaldehyde (BY, 63.6 mg, 0.3 mmol), benzoic anhydride (45.1 mg, 0.2 mmol), and benzoic acid (2.44 mg, 0.02 mmol) were weighed and placed in a 10 mL heat-resistant glass tube. The tube was sonicated for 10 minutes to ensure complete dispersion. Oxygen was then removed from the tube through three freeze-evacuation-thawing cycles, and the tube was sealed. The reaction mixture was placed at 180 °C for 5 days. After the reaction, the mixture was cooled to room temperature, and the resulting solid was soaked in an ammonia-DMF (V / V = 1:1) mixture for one day. It was then purified for one day using a Soxhlet extractor with a methanol and acetone (V / V = 1:1) mixture, and dried under vacuum at 80 °C for 12 hours to obtain well-crystallized COF. TTBYPowder. Then COF TTBY Powder (50 mg) and CuCl2·2H2O (66 mg, 0.39 mmol) were added separately to 7.5 mL of anhydrous ethanol. The two solutions were then mixed and stirred at 25 °C and 1000 rpm for 12 hours. After centrifugation, the resulting product was washed with 50 mL of methanol and dried under vacuum at 80 °C for 12 hours to obtain adsorbent I. The actual copper loading was determined to be 13.8 wt% by ICP-OES.

[0042] Figure 1 The X-ray diffraction patterns of adsorbents A to C and adsorbent D prepared in Examples 1-3 and Comparative Example 1 show that the COFs support has high crystallinity and that copper species exist in an atomically dispersed form.

[0043] Figure 2 a and Figure 2 b represents the N2 adsorption-desorption isotherms and pore size distribution diagrams of adsorbents A to C and adsorbent D prepared in Examples 1-3 and Comparative Example 1, respectively, demonstrating that the materials have high specific surface area and hierarchical pore structure.

[0044] Figure 3 The NH3 adsorption isotherms of adsorbents A to C prepared in Examples 1-3 and Comparative Example 1 with adsorbent D at 25 °C and 1.0 bar show that single-atom sites of metal can achieve multi-molar adsorption capacity.

[0045] Figure 5 The image shows an aberration-corrected HAADF-STEM image of the adsorbent A material prepared in Example 1, where red circles mark copper species existing in single-atom form.

[0046] Figure 6 The Cu K-edge XANES and FT-EXAFS spectra of the adsorbent A material prepared in Example 1 are shown. By comparing with copper foil and copper oxide, its metastable Cu-N2 coordination configuration is confirmed.

[0047] Figure 7 The dynamic breakthrough curves of the adsorbents prepared in Examples 1-3 and Comparative Examples 1-3 at 25 °C for a 75% H2 / 25% N2 mixture containing 100 ppm NH3 demonstrate that they can achieve deep purification of trace amounts of NH3.

[0048] Figure 8 The graph shows the change in NH3 capacity of the adsorbent C material prepared in Example 3 during 30 adsorption-desorption cycles, demonstrating its excellent cycle stability (capacity retention >97%).

[0049] Table 1 shows the stoichiometric ratio of NH3 molecules to Cu sites at 25, 40, 60, and 80 °C in Example 1. As shown in Table 1, the Cu sites exhibit the strongest coordination ability for NH3 at 25 °C, reaching a stoichiometric ratio of 14.51 at 1.0 bar. Even at the same pressure, the stoichiometric ratio remains at 10.75 when the temperature rises to 80 °C. The comparison of data at different temperatures reveals that the effect of temperature increase is more significant in the low-pressure region. For example, at 0.1 bar, the stoichiometric ratio decreases from 7.83 at 25 °C to 4.45 at 80 °C, but still exceeds the traditional stoichiometric ratio of 4. Overall, the adsorption capacity of NH3 increases with increasing pressure and decreases with increasing temperature, consistent with typical exothermic adsorption behavior.

[0050] Table 1 is a statistical table of the stoichiometric ratio of NH3 molecules to Cu sites adsorbed at 25, 40, 60, and 80 °C in Example 1.

[0051]

[0052] Table 2 shows the structural parameters of the adsorbents prepared in Examples 1-3.

[0053]

[0054] As shown in Table 2, the structural parameters of the prepared adsorbent exhibit a regular change with the increase of metal loading, among which the specific surface area increases from 1339 m². 2 / g (Example 1) decreased to 10¹² m 2 / g (Example 3). Example 1 had the highest pore volume and average pore size, reaching 0.59 cm. 3 / g and 1.8 nm. These structural parameters directly affect the mesoporous structure and active site distribution of the adsorbent. The high specific surface area, pore volume and pore size of Example 1 provide the basis for its excellent NH3 adsorption performance and promote mass transfer and molecular diffusion during the adsorption process.

[0055] Application Example 1 An integrated testing system was constructed, consisting of an online ammonia decomposition reactor, an ammonia adsorption purification unit, an online gas analyzer, and a proton exchange membrane fuel cell (PEMFC) connected in series. 20 mL of ammonia decomposition catalyst was loaded into a fixed-bed reactor, and the reactor was heated to 500 °C under atmospheric pressure. After the temperature stabilized, ammonia-containing feed gas was introduced into the catalyst bed. After catalytic decomposition, the ammonia gas produced a mixed gas containing H2, N2, and approximately 100 ppm of residual NH3, with the total outlet gas flow rate controlled above 2.0 L / min. The ammonia decomposition tail gas was continuously passed through a fixed-bed adsorption column packed with 20 mL of adsorbent A at 25 °C and 0.4 MPa for adsorption purification. Simultaneously, a Thermo Scientific Antaris IGS gas analyzer was used to monitor the NH3 concentration in the outlet gas of the ammonia decomposition reactor in real time.

[0056] During PEMFC testing, ammonia decomposition gas (H2 / N2 ≈ 3:1) was introduced at the anode, and air was introduced at the cathode. The stoichiometric ratios of the anode and cathode gases were set to 1.5 and 2.0, respectively. The inlet pressures of the anode and cathode were controlled at 160 and 140 kPa, respectively, and the battery temperature was maintained at 75 °C. Under these conditions, polarization curves and power density curves corresponding to different fuel systems were tested, and the changes in battery voltage, current density, and power density with operating conditions were recorded. Battery durability testing was performed using a 1.0 A / cm² pressure. 2 In constant current discharge mode, the battery voltage change over 120 minutes was continuously recorded. Figure 9 The performance comparison chart shows the ammonia-hydrogen fuel cell system using adsorbent A prepared in Example 1. Compared to the baseline H2 / N2 mixture, the ammonia decomposition gas purified by adsorbent A exhibits similar voltage and current output, while the voltage is significantly lower at the same current density when using unpurified ammonia decomposition gas. After adsorption purification, the peak power density of the fuel cell increases from 0.45 W / cm³. -2 Increased to 1.1 W cm -2 above.

[0057] After the tests, fresh membrane electrode assemblies (MEAs) and MEAs that had been in contact with unpurified fuel gas and fuel gas purified by the catalyst prepared in Example 1 were collected, and their ion exchange capacity, proton conductivity, and tensile strength were tested. The ion exchange capacity of the membrane was determined by acid-base titration: the membrane sample dried to constant weight was converted into H+. + The H₂ released after ion exchange with NaCl solution was titrated with standard NaOH solution. +The proton conductivity was determined using the AC impedance method and calculated based on the membrane resistance and sample geometry. The mechanical properties of the membrane were assessed using a universal testing machine with uniaxial tensile testing. Stress-strain curves were recorded, and tensile strength was calculated. After operation with unpurified ammonia decomposition tail gas, the tensile strength of the MEA (Membranes in Assay) significantly decreased; however, when operating with adsorbent A to purify the fuel, the tensile strength of the MEA remained close to its initial level, indicating that adsorption purification effectively mitigates the damage of ammonia to the mechanical properties of the MEA.

[0058] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should be included in the scope of the present invention.

Claims

1. A method for preparing a metal single-atom covalent organic framework material, characterized in that: Includes the following steps: (1) 2,4,6-trimethylpyridine, terephthalaldehyde, benzoic anhydride and benzoic acid were reacted under nitrogen protection for a period of time. After the reaction was completed, the mixture was cooled to room temperature. The resulting solid was soaked, purified and dried to obtain a covalent organic framework material. (2) The covalent organic framework material is mixed with the metal salt in a solvent and impregnated. Then, after centrifugation, washing and drying, a metal single-atom covalent organic framework material is obtained.

2. The preparation method according to claim 1, characterized in that: The molar ratio of 2,4,6-trimethylpyridine, terephthalaldehyde, benzoic anhydride and benzoic acid in step (1) is 0.2-0.4:0.3-0.6:0.2-0.4:0.02-0.

04.

3. The preparation method according to claim 1, characterized in that: The reaction time in step (1) is 3-7 days and the reaction temperature is 160-200℃.

4. The preparation method according to claim 1, characterized in that: The metal salt mentioned in step (2) is a chloride, nitrate, acetate or sulfate of copper, zinc or cobalt.

5. The preparation method according to claim 1, characterized in that: The immersion temperature in step (2) is 0-50℃, the stirring speed is 500-1500 rpm, and the treatment time is 1-48 hours.

6. The preparation method according to claim 1, characterized in that: The solvent mentioned in step (2) is one or more of methanol, ethanol or isopropanol.

7. A metal single-atom covalent organic framework adsorbent material, characterized in that: The material is prepared by any one of claims 1-6, and comprises a covalent organic framework carrier and a metal single atom anchored thereon; wherein the metal single atom forms a metastable coordination structure with the framework nitrogen atom, which can undergo configurational migration when ammonia is adsorbed.

8. The metal single-atom covalent organic framework adsorbent material according to claim 7, characterized in that: The loading amount of the metal single atom on the covalent organic framework support is 1wt%-20wt%.

9. The application of the metal single-atom covalent organic framework material as described in any one of claims 7-8 in gas adsorption or separation, characterized in that: The gas is ammonia; the application is to separate or capture ammonia from a mixed gas, which is the tail gas from the decomposition of ammonia to produce hydrogen, containing hydrogen, nitrogen and trace amounts of ammonia; the concentration of the trace amounts of ammonia is 50-200 ppm.

10. The application of the metal single-atom covalent organic framework material as described in any one of claims 7-8 in proton exchange membrane fuel cells.